Pakistan : Fourth Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility and Request for Waiver of Performance Criterion. (IMF Staff Country Reports; Country Report ;, 2003)
This paper examines Pakistan's Fourth Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility and Request for Waiver of Performance Criterion. Progress on the structural front through November 2002 was broadly in line with the program, except for the power sector, but weakened in the subsequent months. All quantitative performance criteria for end-September 2002 were met. The authorities have requested a waiver for the nonobservance of the continuous structural performance criterion regarding tax exemptions.